Instilling literacy through Developmental Module Approach (DMA) - Dali, Mohd Hasani; Shaari, Abdull Sukor; Ghazali, Mohd Izam; Yusoff, Nuraini (2012)
Development of module has great impact on literacy today. This paper highlights the challenges and experiences of the researchers in an academic institution where the research project which initially began as part of an academic research initiative expanded to helping a marginalized community in need.Literacy pedagogy has to be relevant to the needs of the pupils who come from diverse contexts.As such there is a need for a method and module to design an appropriate pedagogy to improve literacy among these pupils.In this paper, we share the conception of instilling literacy by utilizing the Developmental Module Approach (DMA), an example of a systematic approach in improving literacy among a group of indigenous pupils specifically the Semai community from Terisu in Cameroon Highland,Pahang.In contrast, Malay Language is used as a medium in teaching across schools in Malaysia including elementary school of Orang Asli and a more significant second language use in the classroom by Orang Asli pupils. The finding has provided important insights for the development of the pedagogical module and may offer a clear understanding of reasons Orang Asli pupils lag behind in their academic attainment.Based on the interviews we found that among the problems faced in the Malay Language literacy are closely related to cultural and environment issues and how such disparities affect drop-out rate among Orang Asli pupils.The study is expected to provide input to the curriculum development center, educational administrators and teachers.